2004
DOI: 10.1051/0004-6361:20041001-1
|View full text |Cite
|
Sign up to set email alerts
|

Model of the ablation of faint meteors

Abstract: Abstract.A model of meteor ablation in the atmosphere has been developed for meteoroids in the mass range 10 −12 kg to 4 × 10 −5 kg (size range 10 µm to 2 mm). The model builds on the classical model of meteor ablation, and adds a thermal fragmentation mechanism. The goal of the model is to characterize the physical structure (fundamental grain sizes) and chemical composition of meteoroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(160 citation statements)
references
References 19 publications
2
158
0
Order By: Relevance
“…We were able to compute the bulk density of 92 meteoroids using a model of meteor ablation based on the work of Campbell- Brown & Koschny (2004), where we required that the complete observed lightcurve and deceleration be fitted simultaneously to the modeled lightcurve and deceleration. We found that our values of bulk density covered the entire range of possible meteoroid bulk density values: from very porous cometary bodies (low density) to very high values, consistent with asteroidal bodies made largely of iron in some form.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We were able to compute the bulk density of 92 meteoroids using a model of meteor ablation based on the work of Campbell- Brown & Koschny (2004), where we required that the complete observed lightcurve and deceleration be fitted simultaneously to the modeled lightcurve and deceleration. We found that our values of bulk density covered the entire range of possible meteoroid bulk density values: from very porous cometary bodies (low density) to very high values, consistent with asteroidal bodies made largely of iron in some form.…”
Section: Resultsmentioning
confidence: 99%
“…We use the dustball model of Campbell- Brown & Koschny (2004). It uses the Clausius-Clapeyron formalism to consider mass loss before the boiling temperature is reached, and allows the user to define the number and size of constituent grains.…”
Section: Ablation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The height of ablation is influenced by many factors, including the entry angle, the speed of the meteoroid, its mass, the energy required to ablate the material of which it is composed, its boiling point, its structure, and its bulk density (Campbell-Brown & Koschny 2004).…”
Section: Introductionmentioning
confidence: 99%